Valores e qualidade de vida no trabalho: estudo de caso em uma rede supermercadista - Silva, Diana Della Méa da (2013)
It is noticeable, currently, a market dynamics that is highly competitive and demanding. Upon facing such perception, studies are conducted to seek an understanding of organizational processes, in order to make them more dynamic and applicable. Within this perspective, this study aims to analyze some Values related to Work and Life Quality at Work from the point of view of the employee. It is known that the dynamics of today's society is dependent on working and this fact provides some elements for this study, as it allows an analysis of the relationships between subjects and their work, with an opportunity for an alignment of expectations and the search for continuous improvements in the productive development. With an exploratory- descriptive character, this study presents a quantitative approach to the problem, and as a technical procedure, it was carried out a case study in a supermarket chain in Santa Maria, RS, with a population of one hundred forty-two employees grouped in administrative functions. Data gathering was performed by means of a questionnaire consisting of three instruments: the first, for identifying the profile of the respondents, followed by a questionnaire formatted for the Brazilian reality, the model developed by Porto and Tamayo (2003), Value Scale relating to Labor, and, finally, the application of Reis Junior model (2008), QWLQ -78 (Quality of Working Life Questionnaire) also adapted for Brazil on Life Quality at Work. For the analysis of these data, they were organized into a spreadsheet in Excel (Office 2003) and, subsequently, analyzed with the aid of the Statistical Analysis System software (version 9) and Statistical Package for Social Sciences (version 21). This collaborated for the measurement, organization and crossing of the variables obtained, which provided some information on (average) descriptive tendency measures and dispersion measures (standard deviation), as well as the analysis of Pearson correlations. The results show a moderate positive and significant correlation (r = 0.3819, p = 0.00). This means that the higher the quality of life is, more value will be assigned to work by the staff analyzed.